Anionic glycolipids related to glucuronosyldiacylglycerol inhibit protein kinase Akt. Issue 4 (24th November 2014) - Vetro, Maria; Costa, Barbara; Donvito, Giulia; Arrighetti, Noemi; Cipolla, Laura; Perego, Paola; Compostella, Federica; Ronchetti, Fiamma; Colombo, Diego
Abstract : Long chain GlcADG analogues synthesized as PI3P mimics inhibited isolated Akt and proliferation of human ovarian carcinoma IGROV-1 cells. Abstract : New glucuronosyldiacylglycerol (GlcADG) analogues based on a 2- O -β-d -glucopyranosyl- sn -glycerol scaffold and carrying one or two acyl chains of different lengths have been synthesized as phosphatidylinositol 3-phosphate (PI3P) mimics targeting the protein kinase Akt. The Akt inhibitory effect of the prepared compounds was assayed using an in vitro kinase assay. The antiproliferative activity of the compounds was tested in the human ovarian carcinoma IGROV-1 cell line in which we found that two of them could inhibit proliferation, in keeping with the target inhibitory effect.